2016
DOI: 10.1371/journal.pone.0154002
|View full text |Cite
|
Sign up to set email alerts
|

The Quantum Nature of Drug-Receptor Interactions: Deuteration Changes Binding Affinities for Histamine Receptor Ligands

Abstract: In this article we report a combined experimental and computational study concerning the effects of deuteration on the binding of histamine and two other histaminergic agonists to 3H-tiotidine-labeled histamine H2 receptor in neonatal rat astrocytes. Binding affinities were measured by displacing radiolabeled tiotidine from H2 receptor binding sites present on cultured neonatal rat astrocytes. Quantum-chemical calculations were performed by employing the empirical quantization of nuclear motion within a cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 66 publications
(55 reference statements)
5
45
0
Order By: Relevance
“…These findings do not argue for the irrelevancy of isotopic exchange, but do relegate the majority of this concern to binding. Isotope effects on the binding of a ligand with a protein have been examined extensively (85,86) and were the subject of a recent paper on the H2 histamine receptor (58). Whereas Kržan et al (58) detected small alterations in the binding of ligand to receptor due to isotope exchange and conclude with possibly relevant comments concerning the VTO, we considered both the affinity and the functional activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings do not argue for the irrelevancy of isotopic exchange, but do relegate the majority of this concern to binding. Isotope effects on the binding of a ligand with a protein have been examined extensively (85,86) and were the subject of a recent paper on the H2 histamine receptor (58). Whereas Kržan et al (58) detected small alterations in the binding of ligand to receptor due to isotope exchange and conclude with possibly relevant comments concerning the VTO, we considered both the affinity and the functional activity.…”
Section: Resultsmentioning
confidence: 99%
“…Isotope effects on the binding of a ligand with a protein have been examined extensively (85,86) and were the subject of a recent paper on the H2 histamine receptor (58). Whereas Kržan et al (58) detected small alterations in the binding of ligand to receptor due to isotope exchange and conclude with possibly relevant comments concerning the VTO, we considered both the affinity and the functional activity. By considering both aspects, we are able to draw conclusions regarding the activation of the proteinaddressing the VTO directly-while retaining knowledge of possible binding effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Potentially, one can use this chemical shift to monitor the R – PP stacking effect on the h‐bond. Recently, it has also been shown that deuteration can affect the binding of small molecules to a protein presumably through perturbing h‐bonds . This isotope effect may provide new insight into h‐bond interactions and some hint in the cooperativity study.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the patch clamp technique cannot be used as the basis of an imaging modality. Fluorescence based techniques, on the other hand, are plagued by concerns over the relative inertness of the molecular label and are generally ill‐equipped for dynamically resolving surface specific interactions in multi‐membrane cells.…”
Section: Introductionmentioning
confidence: 99%